Purification and Immunological Characterization of Riboflavin Binding Protein (RFBP) from Different Avian Eggs - G.RAJENDER; G.BENARJEE (International Journal of Pharma and Bio Sciences, 2010)
Riboflavin binding protein (RfBP) was isolated first time in India from peacock eggs (Pavo cristatus), Hen eggs (Gallus gallus). The Rfbp was purified in two steps, DEAE-Sephadex A-50 ion exchange chromatography. The final purification of proteins (Rfbp) was achieved on sephadex G-100.The protein content was estimated with Lowry method. The purity of the proteins was judged by cylindrical and slab–gels, SDS-PAGE techniques. These proteins showed a single band on SDS gels and the molecular weight was 30 Kilodaltons. Antiserum was raised against these Rfbp’s in rabbit. This antiserum showed Immunological cross reactivity (precipitation line) between the two compounds. This study proved that, these two birds (Peacock, Hen) are immunologically relative and phylogentically different from each other.